FTO genotype was associated with breast cancer in HER2 negative patients. (June 2022) - Montazeri, Fateme; Hatami, Hossein; Fathi, Soroor; Hasanpour Ardekanizadeh, Naeemeh; Bourbour, Fatemeh; Rastgoo, Samira; Shafiee, Fatemeh; Akbari, Mohammad Esmail; Gholamalizadeh, Maryam; Mosavi Jarrahi, Seyed Alireza; Doaei, Saeid
Summary: Background: The fat mass and obesity-associated (FTO) gene may influence the risk of breast cancer (BC). The single nucleotide polymorphisms (SNPs) of FTO gene may exert different impacts on different types of BC. In this study, we investigated the association between FTO SNP rs9939609 and the status of estrogen receptor (ER), progesterone receptor (PR), P53, and human epidermal growth factor receptor-2 (HER-2) in BC patients. Methods: Our case–control study was included 540 Iranian participants aged 35 to 70 (180 women with BC as the case group and 360 healthy controls). After genotyping for risk allele rs9939609 of the FTO gene, a logistic regression was applied to elucidate the association between FTO SNP rs9939609 and BC risk based on the receptor status. Results: The number of HER-2 negative patients was significantly higher in FTO rs9939609 risk allele carrier group (61.5% vs. 41.4%, P < 0.05). A significant association was found between BC and rs9939609 FTO gene polymorphism only in HER2 negative BC patients (OR = 1.79, CI95%: 1.2–3.56, P = 0.03). No association was identified between FTO rs9939609 polymorphism and the status of ER, PR, and P53. Conclusion: We indicated that FTO SNP rs9939609 can be a potential therapeutic target particularly in HER-2 negative BC cases. The importance of this risk allele in BC pathogenesis needs to be further highlighted.